System Interventions for Improving Water and Land Productivity of Sone Canal - Gautam, U.S.; Singh, S.R.K.; Singh, D.K. (Indian Journal of Extension Education, 2010)
In Bihar 87 per cent farmers come under marginal and small categories including share croppers due to unawareness about latest recommendation and technologies. The average productivity of the rice and wheat is 2 t/ha and 1.9 t/ha respectively. Which is less then the national average yield of rice and wheat i.e. 2.05t/ha and 2.7t/ha respectively. The prevailing practice of late transplanting severely fails to exploit potential rainfall in rice cultivation results in heavy loss of water, soil and nutrients through excess run-off. The late rice harvesting delaying the wheat sowing, which takes place very late up to first week of January, severely reduce the yield of wheat. Keeping afore-mentioned production constraint, the study was conducted with objective of system interventions for improving water and land productivity of Sone Canal. The impact of system interventions reported that the area under improved cultivation of rice & wheat was increased from 2.5 ha to 20 ha in four villages in first years. In 2004, the spread has been found to be 200 villages for rice crop. Farmers' motivation and function of Water User Association was found to be geared up due to such intervention package. This enabled efficient use of water and use of quality inputs and scientific operation for crop cultivation.